If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j(x) = 2x + 9 Multiply j * x jx = 2x + 9 Reorder the terms: jx = 9 + 2x Solving jx = 9 + 2x Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Divide each side by 'x'. j = 9x-1 + 2 Simplifying j = 9x-1 + 2 Reorder the terms: j = 2 + 9x-1
| 3a+12=4a+7 | | 6.2=w+5.91 | | 2(4x-3)-8=36 | | -6(4x+2)=-276 | | t=8(76) | | 1.795+x=9.7 | | -5x-8(8x-2)=16 | | 2d+6=3d+2 | | 899+90= | | 1+90= | | 13x+4=3x+20 | | (4x-5)+9=2 | | h(x)=12/x | | 64+4x=148 | | 14=3n+8 | | -28=7(k+3) | | d+0.87=1 | | -(x+20)=17+x | | 7y+51=100 | | 19.6+x=3.6 | | 4q-8+9-5(q+7)=10 | | -4(-8+x)=-8 | | 4.78=0.15x+0.58 | | (3x-82)160=180 | | 0.4+t=1.9 | | 18=2x^3+x | | 6x/4=8/12 | | 5x+10=6x-15 | | 6x-8(4)= | | 63+-3=-3+6n+-3 | | 4(1-h)=6 | | x^2+13x=24 |